Lymphocutaneous Sporotrichosis in a Patient with Underlying Systemic Lupus Erythematosus (Journal of Medicine, 2019)
Sporotrichosis is a globally prevalent subcutaneous mycosis commonly acquired through traumatic inoculation. A 66-year-old woman with underlying systemic lupus erythematosus (SLE) presented initially with a painful non-healing nodule on her right thumb. There was no history of traumatic contact with soil, plants or animals. She was started on an antibiotic but developed multiple nodules on her right forearm which appeared to spread proximally. Culture of her skin biopsy specimen yielded Sporothrix schenckii. The lesions were successfully treated with oral itraconazole. In conclusion, a history of traumatic inoculation need not always be present in SLE patients with sporotrichosis and obtaining a laboratory diagnosis is crucial for those presenting with nodular skin lesions that spread proximallyJ MEDICINE JAN 2020; 21 (1) : 59-61